The impact of information and communication technology (ICT) on the dynamic capabilities of supply chains - Wen-Liang Liu; Chih-Hsing Wang; Kai-Ping Huang (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This study aimed at empirically examining the impact of information and communication technology interaction intensity among supply chain members on the dynamic capabilities of organizations. The study took Taiwan's top 1000 manufacturers as the study population, whereas the relationship between the manufacturers and their suppliers was taken as the research unit, and the respondents consisted of the executives or senior procurement specialists dealing with suppliers in the organizations. LISREL was used to verify models and test their goodness-of-fit. In the data analysis, the parameters were estimated with the default maximum likelihood estimation method. Empirical results of this research can help businesses take a closer look into how the intensity of supply chain ICT interaction impacts the dynamic capabilities of the supply chain members, so that businesses can hold on to different intensities of their supply chain ICT interactions to increase the relationship commitment and trust among the supply chain members, and further promote their dynamic capabilities.
Keywords: L91; O14; 330; Supply chain; Information and Communication Technology (ICT); relationship quality; dynamic capabilities; interaction intensity